Impact of Capital Structure on Performance of Commercial Banks in Nigeria - Nwude, E. Chuke; Anyalechi, Kenneth Chikezie (International Journal of Economics and Financial Issues, 2018)
The study evaluated the influence of financing mix on the performance of commercial banks, and the causal link between debt-equity ratio. Data collated were analyzed using correlation analysis, pooled OLS regression analysis, fixed effect panel analysis, random effect panel analysis, granger causality analysis, as well as post estimation test such as restricted f-test of heterogeneity and Hausman test. The findings show that while debt finance exert negative and significant impact on return on asset, the debt-equity ratio has positive and significant influence on return on equity. There was neither unidirectional nor bidirectional relationship between capital structure and performance of commercial banks in Nigeria. Keywords: capital structure, commercial banks, Nigeria JEL Classifications: G21, G3, G32